Determining the zone of impact of norovirus contamination in shellfish production areas through microbiological monitoring and hydrographic analysis. (1st November 2017) - Campos, Carlos J.A.; Goblick, Gregory; Lee, Ron; Wittamore, Ken; Lees, David N.
Abstract: Norovirus (NoV) contamination of filter feeding bivalve shellfish is a well-recognised human health threat when shellfish are grown in sewage polluted waters. To date, the identification of high risk zones around sewage discharges in shellfish production areas (SPAs) has not been based on NoV data. This study utilised molecular methods for NoV analysis, combined with hydrographic studies, to determine the relationship between NoV concentrations in shellfish and sewage effluent dilution. Cages with mussels and oysters were placed at different distances downstream of sewage discharges in two coastal sites in England. The shellfish were tested for concentrations of NoV (genogroups I and II) and E. coli . Drogue tracking and dye tracing studies were conducted to quantify the dispersion and dilution of sewage effluent in the SPAs. Significant negative associations were found between both total concentrations of NoV (GI + GII) and E. coli and sewage effluent dilution in the SPAs. The total NoV concentrations predicted by the model at 300:1, 1000:1 and 5000:1 ratios of estuarine water to sewage effluent were 1200; 600; and 200 copies/g, respectively. The estimated area of NoV contamination varied according with local pollution source impacts and hydrographic characteristics. The results help to inform the derivation of sewage discharge buffer zones as a control measure for mitigating risk from human NoV contamination in SPAs. Graphical abstract: Highlights: Norovirus and E. coli monitoring in two shellfish production areas. Rhodamine tracer studies to evaluate sewage effluent dispersion and dilution. Norovirus levels in shellfish decreased as sewage effluent dilution increased. Different sewage discharge buffer zones in different coastal environments.